2013
DOI: 10.17310/ntj.2013.1.02
|View full text |Cite
|
Sign up to set email alerts
|

State Earned Income Tax Credits and Participation in Regular and Informal Work

Abstract: This paper examines how low-income single parents alter their regular and informal labor supply in response to the earned income tax credit (EITC). Variation in state EITCs from 1997-2005 identifi es changes in informal and regular labor supply of unmarried low-income parents in response to tax credits. The informal-sector participation of single fathers declines by 7.3 percentage points, conditional on working in the regular sector, if a state EITC increases by 10 percent of the federal credit. Regular-sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Based on the success of earlier policy changes, other researchers have proposed that the program should be expanded for both families with one child as well as for childless families (Hoynes 2014;Marr et al 2014). This study shows that the health benefits are largest for people in the plateau phase of the EITC schedule, which has been shown to provide pure income effects (Athreya et al 2010;Gunter 2013). This indicates that, if government policy provides cash transfers that are not conditional on earned income, the relevant effects on health status will correspond to the estimate show in Panel B of Table 7.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Based on the success of earlier policy changes, other researchers have proposed that the program should be expanded for both families with one child as well as for childless families (Hoynes 2014;Marr et al 2014). This study shows that the health benefits are largest for people in the plateau phase of the EITC schedule, which has been shown to provide pure income effects (Athreya et al 2010;Gunter 2013). This indicates that, if government policy provides cash transfers that are not conditional on earned income, the relevant effects on health status will correspond to the estimate show in Panel B of Table 7.…”
Section: Discussionmentioning
confidence: 50%
“…Previous research on the program has established that households in the phase-in part of the schedule increase their employment on the extensive margin following changes to the EITC (Eissa and Liebman 1996;Eissa et al 2008;Meyer 2010). On the other hand, earlier work has shown that household in the middle of the schedule receiving something close to a pure income effect because of little to no change in the number of hours worked (Athreya et al 2010;Gunter 2013). To my knowledge, no previous study has examined whether the effects of EITC changes on health outcomes differ across the three parts of the schedule.…”
Section: Robustness Checksmentioning
confidence: 91%
See 1 more Smart Citation
“…A large body of research for developed economies has studied how individuals respond to welfare policies, in particular, on the labor supply margin (see for instance the surveys in Moffitt, 2003, Ben-Shalom et al, 2011. The responses along additional margins, such as registered and unregistered employment, have received less attention in the literature on developed countries, although there is some evidence that programs that subsidize work based on declared earnings, such as the EITC in the United States, induce low income individuals to shift hours from informal to registered employment (Gunter 2013), in particular among the self-employed (LaLumia, 2009). As discussed above, a series of studies based on credible identification strategies have analyzed the labor market responses to conditional cash transfer programs in developing countries, specifically in regards to labor supply (Alzua et al, 2012, Banerjee et al, 2015, Imbert and Papp, 2015, registered employment , and choices between formal and informal work (Garganta and Gasparini, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Resource constraints create what the World Bank has called a "vicious cycle, in which inadequate resources restrain output and undermine the quality of statistics, while the poor quality of statistics leads to lower demand and hence fewer resources" (World Bank, 2002, para 11). Complicating the effects of the so-called "vicious cycle" are the remnants of tumultuous economic times that spur difficult-to-monitor informal and black market economies (Jerven 2013;Gunter 2013).…”
Section: National Statistical Capacitymentioning
confidence: 99%